Patient empowerment and engagement with a health infomediary. Issue 1 (March 2017) - Khuntia, Jiban; Yim, Dobin; Tanniru, Mohan; Lim, Sanghee
Abstract: Objectives: This study explores the role of three types of empowerment, psychological, discretionary, and leadership, on sustained engagement with a health infomediary. Discretionary empowerment refers to authority, psychological empowerment is the manifestation of inherent motivation and response, and leadership empowerment is the trait of knowledge-based control and governance for a group in an infomediary. Sustained engagement is critical for patients to derive long-term benefits from an infomediary. Relationships between the three types of patient empowerments on sustained patient engagement is conceptualized and operationalized with testable hypotheses. Methods: Data from a health infomediary providing a knowledge exchange platform for patients interested in cosmetic surgery was obtained through the website. Probit regression models were used to test hypotheses using daily activity observations of 21, 715 patients during the first 30 and 60 days of their engagement with the infomediary platform. Results: All three empowerment types have positive association with sustained engagement. In addition, leadership empowerment is shown to play a higher role than discretionary or psychological empowerments in sustaining patient engagement. Conclusions: Identifying empowered patients is likely to benefit health infomediaries. Leadership empowerment has a greater role than discretionary or psychological empowerments in sustaining patient engagement with infomediaries. Incentive structures around promoting patients towards leadership empowerment are likely to generate positive returns for health infomediaries. Highlights: Health infomediaries help in patient empowerment. Focus is on identification of types of empowerment: psychological, discretionary, and leadership. Comparative assessment of the influence of types of empowerment on sustained engagement with a health infomediary. Analysis of 65, 000 daily activity observations of 21, 715 patients in the first 30 and 60 days of their infomediary use. Leadership empowerment is found to have a higher continued effect on sustained engagement, followed by discretionary and psychological empowerments.